Online EFL Teaching and Learning: Different Skills, Different Challenges - Ermawati Ermawati; Nur Fadillah Nurchalis; Ahmed Sardi (Institut Agama Islam Negeri Palopo, 2021)
Online EFL teaching and learning has been described as a viable method of dealing with the pandemic. Only a few studies have focused on teachers' expectations as an important component of teaching effectiveness. As a result, the aim of this study is to ascertain teachers' perceptions of teaching English skills digitally, as well as their difficulties in dealing with them. The qualitative analysis approach was used in this sample, with three English teachers serving as respondents. It collects data through in-depth interviews. Data is compiled, transcribed, and sorted according to the primary topic of each sentence. The findings revealed that EFL teachers faced a number of difficulties when teaching English skills online.Teachers struggle to find adequate resources for listening, depend exclusively on YouTube, have difficulty recognizing students' comprehension, and do not consider last-year students to be relevant. In general, the internal network does not accept video conferences, there is a lack of feedback, and it is a time-consuming operation. Teachers find it difficult to monitor their students' reading activity, loss of reading abilities, more student-centered attitude, and poor attendance in class when it comes to reading. Finally, pupils are unable to write proper sentences, and teachers do not provide any critical thinking activities. It has also been discovered that the receptive abilities of listening and reading are the most difficult to develop in relation to online learning.